Genome-Wide Transcriptional Start Site Mapping and sRNA Identification in the Pathogen Leptospira interrogans - Zhukova, Anna; Fernandes, Luis Guilherme; Hugon, Perrine; Pappas, Christopher J.; Sismeiro, Odile; Coppée, Jean-Yves; Becavin, Christophe; Malabat, Christophe; Eshghi, Azad; Zhang, Jun-Jie; Yang, Frank X.; Picardeau, Mathieu (Frontiers in Cellular and Infection Microbiology, 2017)
Leptospira are emerging zoonotic pathogens transmitted from animals to humans typically through contaminated environmental sources of water and soil. Regulatory pathways of pathogenic Leptospira spp. underlying the adaptive response to different hosts and environmental conditions remains elusive. In this study, we provide the first global Transcriptional Start Site (TSS) map of a Leptospira species. RNA was obtained from the pathogen Leptospira interrogans grown at 30°C (optimal in vitro temperature) and 37°C (host temperature) and selectively enriched for 5′ ends of native transcripts. A total of 2865 and 2866 primary TSS (pTSS) were predicted in the genome of L. interrogans at 30 and 37°C, respectively. The majority of the pTSSs were located between 0 and 10 nucleotides from the translational start site, suggesting that leaderless transcripts are a common feature of the leptospiral translational landscape. Comparative differential RNA-sequencing (dRNA-seq) analysis revealed conservation of most pTSS at 30 and 37°C. Promoter prediction algorithms allow the identification of the binding sites of the alternative sigma factor sigma 54. However, other motifs were not identified indicating that Leptospira consensus promoter sequences are inherently different from the Escherichia coli model. RNA sequencing also identified 277 and 226 putative small regulatory RNAs (sRNAs) at 30 and 37°C, respectively, including eight validated sRNAs by Northern blots. These results provide the first global view of TSS and the repertoire of sRNAs in L. interrogans. These data will establish a foundation for future experimental work on gene regulation under various environmental conditions including those in the host.